1998
DOI: 10.1063/1.869722
|View full text |Cite
|
Sign up to set email alerts
|

The nonlinear evolution of centrifugal instabilities in curved, compressible mixing layers

Abstract: The nonlinear development of Görtler vortices in a curved compressible mixing layer is studied. It has been shown both experimentally and theoretically that the curved mixing layer can support a centrifugal mode, which is believed to be similar to the Görtler vortex. This study follows the corresponding incompressible study of Seddougui & Otto [Proceedings of the IUTAM Symposium on Nonlinear Instability and Transition in Three-Dimensional Boundary Layers, edited by P. W. Duck and P. Hall (Kluwer Academic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The problem can be extended to suit a nonlinear investigation on the effect of the curvature for both the stably curved and the unstably curved wake-dominated curved compressible mixing layers. This has been considered in the absence of a wake by Owen et al 8 Having studied the behavior of the Görtler vortex, it would be interesting to conduct a similar investigation on the Kelvin-Helmholtz and Rayleigh-Taylor instabilities within the wake-dominated curved compressible system to study how the modes of these instabilities behave when both stably and unstably curved wake-dominated mixing layers are considered.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The problem can be extended to suit a nonlinear investigation on the effect of the curvature for both the stably curved and the unstably curved wake-dominated curved compressible mixing layers. This has been considered in the absence of a wake by Owen et al 8 Having studied the behavior of the Görtler vortex, it would be interesting to conduct a similar investigation on the Kelvin-Helmholtz and Rayleigh-Taylor instabilities within the wake-dominated curved compressible system to study how the modes of these instabilities behave when both stably and unstably curved wake-dominated mixing layers are considered.…”
Section: Discussionmentioning
confidence: 97%
“…IV and verified using the alternative method provided in OSO. 8 The variation in the growth rate of the first mode, ␤ = ␤ 1 , for a particular wave number, a = 5, for both the stably and the unstably curved compressible mixing-layer system under increasing wake effect is demonstrated in Fig. 12͑a͒.…”
Section: Numerical Wake Flow Model Predictionmentioning
confidence: 97%
See 1 more Smart Citation
“…In Owen, Seddougui & Otto (1998), which follows the incompressible study of Seddougui & Otto (1995), the nonlinear structure of the centrifugal instabilities was investigated. The calculation was affected in the parameter régime corresponding to the neighbourhood of the right-hand branch of the neutral curve.…”
Section: Introductionmentioning
confidence: 99%
“…It was found in both papers that the predominantly velocity-driven mode had the effect of reducing the temporal growth rates of the inviscid Rayleigh modes. However, Owen et al (1998) found that the presence of the thermal modes produced a destabilization of the inviscid modes, see Otto, Sarkies & Denier (2000).…”
Section: Introductionmentioning
confidence: 99%